Population structure of the primary gene pool of Oryza sativa in Thailand - Pusadee T. (2014)
The gene pool of cultivated Asian rice consists of wild rice (Oryza rufipogon Griff.), cultivated rice (O. sativa L.) and a weedy form (O. sativa f. spontanea). All three components are widespread in Thailand, frequently co-occurring within fields and providing the opportunity for gene flow and introgression. The purpose to this study is to understand the on-going evolutionary processes that affect the gene pool of rice by analysis of microsatellite variation. Results indicate that O. rufipogon, the wild ancestor of rice, has high levels of genetic variation both within and among populations. Moreover, the variation is structured predominantly by annual and perennial life history. High levels of variation are detected among cultivars indicating Thai cultivated rice has a broad genetic base with only a 20 % reduction in diversity from its wild ancestor. The weedy rice populations reveal varying levels of genetic variation, from nearly as high as wild rice to near zero. Weedy rice is genetically structured into 2 groups. Some populations of invasive weedy rice are the result of hybridization and gene flow between local wild rice and local cultivated rice in the regions of co-occurrence. Other populations of weedy rice are genetically nearly identical to the local cultivated rice. The diversity analysis indicates that the rice gene pool in Thailand is a dynamic genetic system. Gene flow is ongoing among its three main components, first between cultivated and wild rice resulting in weedy rice. Weedy rice in turn crosses with both cultivated varieties and wild rice. © 2012 Springer Science+Business Media Dordrecht.